1983
DOI: 10.1111/j.1745-9125.1983.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Situational Factors in Disputes Leading to Criminal Violence

Abstract: This article examines the interactive process leading to criminal violence. Official data from 159 incidents of homicide and assault that were not committed in conjunction with other crimes and that resulted in incarceration were examined with respect to the actions of offenders, victims, and third parties. These incidents tended to follow systematic patterns. They began with identity attacks, followed by attempts and failures to influence the antagonist. Threats were made and finally the verbal conflict ended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
220
2
16

Year Published

1988
1988
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(243 citation statements)
references
References 17 publications
(10 reference statements)
5
220
2
16
Order By: Relevance
“…Indeed, research suggests that gun violence is intensely concentrated within high-risk populations. 10,11 For example, recent studies in Boston found that from 1980 to 2008, only 5 % of city block faces and street corners experienced 74 % of gun assault incidents 12 and that 50 % of homicide and nearly 75 % of gun assaults were driven by less than 1 % of the city's youth population (aged [15][16][17][18][19][20][21][22][23][24], most of whom were gang involved and chronic offenders. 13 To better understand how gunshot injury is distributed within highrisk populations, we conducted a study to determine whether the risk of gunshot victimization is related to characteristics of one's social networks.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, research suggests that gun violence is intensely concentrated within high-risk populations. 10,11 For example, recent studies in Boston found that from 1980 to 2008, only 5 % of city block faces and street corners experienced 74 % of gun assault incidents 12 and that 50 % of homicide and nearly 75 % of gun assaults were driven by less than 1 % of the city's youth population (aged [15][16][17][18][19][20][21][22][23][24], most of whom were gang involved and chronic offenders. 13 To better understand how gunshot injury is distributed within highrisk populations, we conducted a study to determine whether the risk of gunshot victimization is related to characteristics of one's social networks.…”
Section: Introductionmentioning
confidence: 99%
“…Such a one-sided focus creates an incomplete picture of lethal events. Research that directly compares how victims and third parties behave in lethal vs. non-lethal events is virtually nonexistent (Felson and Steadman 1983). Consequently, it remains unclear to what extent event characteristics and actors' behaviour differ in lethal vs. non-lethal events.…”
Section: Introductionmentioning
confidence: 99%
“…Felson and Staff 2010;Pridemore and Eckhardt 2008). Felson and Steadman (1983) found that victims of lethal violence were more likely to be under the influence of alcohol or drugs than victims of non-lethal violence. However, evidence is inconsistent as to whether offenders of lethal violence are more likely to be under influence of substance than offenders of non-lethal violence (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations